STRUKTUR KONVERSASI WACANA DEBAT DALAM INDONESIA LAWYERS CLUB - Arum, Dewi Puspa (Universitas Negeri Surabaya, 2015)
Conversation in relation to pragmatic studies can be analyzed using a variety of theories. One theory used in this study is further conversation analysis approach in this discussion referred to the analysis of conversations. Issues of pause, overlapping speech, and speech shifts often occur in conversations conducted in a large forum speakers lot and there is no clarity regarding the given speech turn. Thus, in this case Indonesia Lawyers Club is an ideal research object for study. In accordance with the focus and objectives described in this study, this kind of research is deskripitif kualitatif. First, a pause in the ILC is divided can be analyzed based on two categories, the first based on the duration, and the second based on the position. Second, the shift of speech in this study can be divided into two major categories, namely couples adjacent speech and speech-shift mechanism. Third, an overlap of speech in this study can be divided into three major categories: (1) overlap the word, (2) overlapping phrases, and (3) and overlapping clause. Overlapping word in this study tended to occur at interrupt condition. Overlapping phrase in this study tended to occur in conditions of stealing. Meanwhile, overlapping clause in this study tended to occur in conditions snatch.